Karakterisasi Lactobacillus spp. yang Diisolasi dari Susu Kambing Etawa untuk Pengembangan Probiotik (CHARACTERIZATION OF LACTOBACILLUS SPP., ISOLATED FROM MILK OF ETAWA GOATS FOR LOCAL PROBIOTIC DEVELOPMENT) - Sintyadewi, Putu Rima; Ramona, Yan; Sujaya, I Nengah (Jurnal Veteriner, 2015)
The objective of this research was to characterize Lactobacillus spp., isolated from milk of Etawagoats for local probiotic development. Total of 23 isolates Lactobacillus spp. were tested for resistance tolow pH conditions, high levels of natrium deoxy cholate, and modified gastric juice conditions. Besidesthat, those isolates were also tested to convert cholic acid (CA) into deoxycholic acid (DCA). Isolate thatshowed the most potential properties for local probiotic development was identified by 16S rDNA analysisusing following amplification of this sequence with primers of 27F and 520R). The results showed that 12isolates were found to be resistant to low pH conditions and to high level of NaDC (0.6 mM). Three of them(Lactobacillus spp. GMA46, Lactobacillus spp. GMA47 and Lactobacillus spp. GMA50) did not convertcholic acid into deoxy cholic acid, indicating that they are safe for human use. Lactobacillus spp. GMA46showed better performance in the gastric juice (a model of gastic and intestinal juice containing pepsin andpancreatin enzymes at pH 2, 3 and 4) simulation test. This GMA46 isolate was identified as L. caseiATCC 334 and L. paracasei subsp. tolerans strain NBRC 15906 with 100% similarity, in term of its 16srDNA nucleotide sequence. The results of this research indicate that Lactobacillus sp. GMA46 is anIndonesian potential probiotic strain, isolated from milk of etawa goats
Keywords: Lactobacillus, milk of etawa goats, probiotic, 16S rDNA